Documentação e comunicação popular: a experiência do CPV - Centro de Pastoral Vergueiro (São Paulo/SP, 1973-1989) - Salles, Paula Ribeiro (2013)
The Centro de Pesquisa e Documentação Vergueiro CPV (Vergueiro Research and Documentation Centre) is well-known for the documentation it has collected during the forty years since it was founded. This study analyses the historical circumstances that made it possible for the CPV to accumulate this documental heritage and describes the politics, ideas and practices of popular documentation and communication followed by the then Centro de Pastoral Vergueiro (CPV) in the 1970s and 1980s. The CPV, founded by Dominicans of the Christ the Worker Community in the south of São Paulo city, always maintained a pluralist political approach, working with trade union activists, community associations and a wide range of grassroots and official organisations in the progressive wing of the Brazilian, Latin American and European Catholic church. The CPV played an important role in the organisation and mobilisation of the social movements that emerged in this period and in the fight to redemocratise Brazil. It implemented a broad programme of popular documentation and communication, understood as educational and political practices linked to the struggles and defence of the working class. The CPV adopted the workers struggles of its time and organised an extensive programme to build and strengthen the communication, documentation and recording of the history of social movements. We chose to conduct a wide-ranging study that describes the CPV s experience, its social and political composition, its participation in the extensive communication and documentation networks and its internal practices in developing an innovative experience of popular documentation. It could be considered to be a model of how to organise a popular documentation centre and produce and distribute popular dossiers and booklets